Surgical vs. nonoperative treatment for acute Achilles' tendon rupture: a meta-analysis of randomized controlled trials - Fan, Lei; Hu, Yunan; Zhou, Leng; Fu, Weili (Frontiers in Surgery, 2024)
BackgroundAcute Achilles tendon rupture (AATR) is common among young individuals. There are various management options available, including conservative treatment, open surgical repair, and minimally invasive treatments. However, the optimal treatment approach remains controversial.PurposeIn this study, we conducted a thorough analysis of the existing literature to compare the clinical outcomes of surgical and nonoperative treatments for patients with AATR by conducting a meta-analysis of randomized controlled trials.Study designMeta analysis; Level of evidence, 1.MethodsEligible trials randomly assigned adults with AATR to surgical or conservative treatment and assessed by three independent reviewers. We searched in PubMed, Embase, and The Cochrane Library. The assessment of risk of bias was conducted by entering the data from each included study into the Revman computer program. Extracted data were meta-analyzed. Heterogeneity was evaluated using the I2 test. Pooled results were expressed as odds ratios, risk ratios (OR), and mean differences (MD).ResultsThe meta-analysis included a total of 14 studies and 1,399 patients, with 696 patients receiving surgical intervention and 703 patients undergoing non-surgical treatment. The follow- up duration ranged from 12 to 30 months. The surgical group was found to have a significantly lower re-rupture rate (OR: 0.30, 95% CI: 0.18–0.54; P < 0.00001), but also had a higher risk of other complications (OR: 3.28, 95% CI: 1.56–6.93, P = 0.002). The surgical group also had significantly abnormal calf (OR: 0.45, 95% CI: 0.26–0.76, P = 0.03). There was no statistically significant difference between the two groups in terms of returning to sports, ATRS, abnormal motion of foot and ankle, unable heel-rise, and torque for plantar flexion.ConclusionThe meta-analysis results indicate that surgical intervention for AATR is associated with a lower re-rupture rate, but a higher risk of other complications. Our assessment of life-quality and functional outcomes also suggests that surgery leads to significantly better outcomes in terms of sick leave, abnormal calf, and torque for plantar flexion. Based on these findings, we recommend that surgery is a preferable option for patients who have a higher risk of re-rupture and require a quick rehabilitation.